Equity research - Bayer ag: the growth path for a pharma titan - Santos, Rui Miguel Pinto dos (2022)
One of Bayer AG’s strongest assets and operational flagship across the globe has been its pharmaceutical division, which comprisesroughly40% of total sales of the group, as of 2020. However, it is now dealing with major business shifts which undermine its the medium-term growth prospects, as its two best-selling products, Xarelto TM and Eylea TM, are on the verge of a patent-cliff. As such, Bayer’s pharmaceutical division has been investing on a promising pipeline of medicines, some with the so-called ‘blockbuster’ potential, such as Nubeq a TM, Fineren oneTM and Elinzanetant TM, while it has too been acquiring independent research and development firms and building up external partnerships as to solidify its own footprint on the cell and gene therapy segment, which is expected to have a CAGR of above 25% and to reach US$48bn market value by 2026.But isn’t that an overly optimistic and linear path? In finding so, on this working paper, we describe some of Bayer and the industry’s main characteristics and challenges in the upcoming years, in light of a valuation model to estimate Bayer AG’s share price as of December 2022.